Relationship Between Waist-To-Hip Ratio and HbA1c Levels Diabetes Mellitus Patients at Community Health Centers in Kupang - Situmorang, William Kevin Nathanael; Setianingrum, Elisabeth Levina; Tunggal, Deif; Lada, Christina Olly (Jurnal Biologi Tropis, 2026)
The prevalence of diabetes mellitus continues to increase, alongside a growing burden of central obesity as a major contributing risk factor. The waist-to-hip ratio (WHR) serves as a practical anthropometric indicator for assessing central obesity, whereas glycated hemoglobin (HbA1c) reflects long-term glycemic control. Nevertheless, the evidence regarding the association between WHR and HbA1c levels remains inconclusive and varies across studies. Research objective to analyze the relationship between waist-to-hip ratio (WHR) and HbA1c levels among patients with diabetes mellitus at primary health care centers in Kupang City. This study employed a cross-sectional design. Venous blood samples were collected to measure HbA1c levels, while waist and hip circumferences were measured to obtain the waist-to-hip ratio (WHR) values. Data were analyzed using the Chi Square test. Result: The respondents were aged 18–59 years. The Chi-Square analysis indicated a non-significant association, with a p-value of 0.067. There was no significant association between waist-to-hip ratio (WHR) and HbA1c levels among patients with diabetes mellitus at community health centers in Kupang City. Glycemic control is influenced not only by anthropometric parameters but also by various other factors, including dietary patterns, sex, physical activity, and lifestyle behaviors.